2018
DOI: 10.1111/jmft.12340
|View full text |Cite
|
Sign up to set email alerts
|

“I'm Still Fighting for the Two of Us”: How Partners of UK Veterans Construct Their Experience of Living with Combat‐Related Trauma

Abstract: There has been little qualitative research into the experiences of UK partners of veterans with PTSD. This study therefore aimed to explore how partners constructed their experiences of living with the condition. Fifteen female partners of male UK veterans were recruited and interviewed. Using a social constructionist thematic analysis, five themes were constructed: the women's need to subdue own emotional and behavioral responses; dilemmas about whether the veteran was unwell or 'bad'; attempts at negotiating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 40 publications
(55 reference statements)
1
10
0
Order By: Relevance
“…Family members also indicated other ways that living with a trauma survivor impacts the way they navigate their environment. Several studies found that partners of trauma survivors experience tension, fear, restraint, vigilance, and worry when around the trauma survivor (Akoondzadeh et al, 2018; Beks, 2016; Chauncey, 1994; Doncaster et al, 2018; Frederikson et al, 1996; Goff et al, 2006; Jacob & Veach, 2005; MacDonell et al, 2010; McCormack et al, 2011; Murphy et al, 2017; Outram et al, 2009; Regehr, 2005; Wiersma, 2003). Regarding feelings of fear or worry, male partners and parents of female survivors of sexual assault also reported fears of upsetting survivors by saying the wrong thing and reported feeling apprehensive of expressing their own reactions to the assault as these expressions could upset or make things worse for the survivor (Emm & McKenry, 1988).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Family members also indicated other ways that living with a trauma survivor impacts the way they navigate their environment. Several studies found that partners of trauma survivors experience tension, fear, restraint, vigilance, and worry when around the trauma survivor (Akoondzadeh et al, 2018; Beks, 2016; Chauncey, 1994; Doncaster et al, 2018; Frederikson et al, 1996; Goff et al, 2006; Jacob & Veach, 2005; MacDonell et al, 2010; McCormack et al, 2011; Murphy et al, 2017; Outram et al, 2009; Regehr, 2005; Wiersma, 2003). Regarding feelings of fear or worry, male partners and parents of female survivors of sexual assault also reported fears of upsetting survivors by saying the wrong thing and reported feeling apprehensive of expressing their own reactions to the assault as these expressions could upset or make things worse for the survivor (Emm & McKenry, 1988).…”
Section: Resultsmentioning
confidence: 99%
“…Partners of veterans also note that public discourse about Vietnam led to increased blame directed at the survivor, partners' increased social isolation (Frederikson et al, 1996;McCormack et al, 2011), and partners' perceived need to serve as a protector of the veteran (Outram et al, 2009). Female partners of veterans also identified the potential harm of public discourse pertaining to expectations that they fulfill a dutiful partner role as they felt this led to stigma, difficulty speaking out about their own experiences, or difficulty attending to their own needs (Doncaster et al, 2018).…”
Section: Other Experiencesmentioning
confidence: 99%
“…However, most deployed personnel return to a family, and understanding their reintegration experiences in the family is critical to inform preventive and therapeutic practices. Furthermore, research indicates that civilian spouses of war veterans may experience emotional struggles and increased risk of mental health challenges as they navigate different family roles in the context of deployment (e.g., wife and mother) (Doncaster, Hiskey, McPherson, & Andrews, ). Hence, this population warrants scholarly attention.…”
Section: Discussionmentioning
confidence: 99%
“…This approach focuses on understanding and theorizing about sociocultural contexts, institutional conditions, events and individual realities that point to potential reasons for the participants’ responses (Braun & Clarke, 2006). Similar to Doncaster et al’s (2018) qualitative study, reflexivity and acknowledgement of each collaborator’s perspective was heavily weighted during the data analysis process. Aligning with the constructionist epistemology, the researchers assumed no “correct” answers within the data since truth was considered to be socially constructed (Doncaster et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Similar to Doncaster et al’s (2018) qualitative study, reflexivity and acknowledgement of each collaborator’s perspective was heavily weighted during the data analysis process. Aligning with the constructionist epistemology, the researchers assumed no “correct” answers within the data since truth was considered to be socially constructed (Doncaster et al, 2018). Given that this study is rooted in the acknowledgment of United States patriarchal histories and systems, a constructionist analysis was most appropriate due to the researchers’ axiology of acknowledging the participant’s subjective experiences and the connection to United States sociocultural contexts (Braun & Clarke, 2019; Taylor & Ussher, 2001).…”
Section: Methodsmentioning
confidence: 99%